Differences in clinical and laboratory biomarkers for short and long‐term respiratory outcomes in preterm neonates. Issue 12 (26th August 2021) - Parad, Richard B.; Breeze, Janis L.; Terrin, Norma; Rogers, Lynette K.; Salafia, Carolyn M.; Greenough, Anne; Davis, Jonathan M.
Abstract: Background: Pulmonary outcome of premature neonates has focused more on short‐term than long‐term respiratory morbidities. Objective: Describe risk factors/biomarkers associated with short‐term (bronchopulmonary dysplasia [BPD]) (supplemental oxygen use at 36 weeks postmenstrual age [PMA]) and longer‐term (chronic respiratory morbidity [CRM]) (respiratory related symptoms, medications, medical/emergency visits, hospitalizations at 6–12 months corrected gestational age [CGA]) respiratory outcomes in a longitudinal cohort. Design/Methods: Neonates born at 24–29‐week gestation were prospectively followed to 6–12‐month CGA. Associations between clinical and laboratory risk factors/biomarkers of BPD and CRM were explored. Results: Of 86 subjects, 94% survived. Outcomes were available for 89% at 36‐week PMA (BPD present in 42% of infants) and 72% at 6–12‐month CGA (CRM present in 47% of infants). For the 54 infants with known outcomes for both BPD and CRM, diagnoses were discordant in 41%. BPD was associated with lower birthweight and birthweight Z‐score for GA, lower Apgar scores, more surfactant doses, higher SNAPPE‐II scores, highest Day 1 inspired oxygen concentration, Day 7 oxygen use, prolonged ventilatory support, bacteremia, necrotizing enterocolitis, and treated patent ductus arteriosus. CRM was associated with lower Apgar scores, Day 7 oxygen use and higher urine vascular endothelial growth factor. Patterns of plasma and urine lipid oxidation products differed in the two outcomes. Conclusion: In this hypothesis generating and exploratory study, BPD and CRM were associated with different risk factors/biomarker patterns. Concordance between these two outcomes was weak. Strategies for reducing CRM should be studied in cohorts identified by appropriate early risk factors/biomarkers. BULLET POINTS: What is the key message? BPD and CRM were associated with different risk factors/biomarkers and agreement between these two outcomes was weak. What does it add to the existing literature? Most literature on preterm neonatal lung disease focuses on short‐term outcomes (BPD). Our data add to gaps in knowledge about biomarkers associated with long‐term respiratory morbidity and their differences from predictors of BPD. What is the impact? Therapies to improve long‐term respiratory outcomes should be studied in neonates with associated risk factors/biomarkers.